A novel methodological approach using superimposed Micro‐CT and STL images to analyze hard and soft tissue volume in immediate and delayed implants with different cervical designs. Issue 10 (23rd September 2018) - Sanz‐Martín, Ignacio; Permuy, María; Vignoletti, Fabio; Nuñez, Javier; Muñoz, Fernando; Sanz, Mariano
Abstract: Objectives: To study the hard and soft tissue volume after placing immediate (IMI) or delayed implants (DLI) with a triangular coronal macro‐design (Test/T) or a conventional cylindrical design (Control/C). Material and Methods: T/C implants were inserted in healed ridges or in fresh extraction sockets of eight beagle dogs. Biopsies were processed for Micro‐CT analysis and dental stone casts were optically scanned to obtain STL files revealing the soft tissue contours at 12 weeks. Image analysis software was utilized to match common landmarks superimposing the two sets of data. Three distinct volumes were calculated; buccal bone volume (B‐BV), soft tissue volume below the implant shoulder (EC‐STV), and the soft tissue volume above the implant shoulder (SC‐STV). Using linear measurements, the soft tissue height (STH), the mucosal thickness (MT‐IS), and the distance from the implant shoulder to the bone crest (I‐BC) were assessed in the digital images and in conventional histology to assess the concordance, reproducibility, and reliability. Results: There were no significant differences between test and control implants regarding the buccal bone volume, although test implants had greater B‐BV in all locations except for PM2. The soft tissue volume was similar at T/C implants. The surgical approach influenced the distribution of the total tissue volume. In the IMI, a low position of the bone crest was correlated with low values of B‐BV, SC‐STV, MT‐IS, and STH. Linear measurements showed a high correlation between the histology and digital measurements and high inter and intra examiner agreement. Conclusion: The superimposition of Micro‐CT/STL allowed the analysis of soft and hard tissue volumes. Reduction of the implant buccal aspect resulted in nonsignificant higher bone volume although similar soft tissue volume while the surgical approach influenced soft tissue response.